Examining the mediating effect of risk control capability of supply chain management on the resilience of public hospitals in China / Zhang Tongtong ... [et al.] - Zhang Tongtong; Zakaria, Nor Balkish; Said, Jamaliah; Joseph Ason, Yvonne; Erum, Naila (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
In the era of volatility, uncertainty, complexity, and ambiguity (VUCA) the frequency of public emergencies is rising. The COVID-19 pandemic has resulted in shortages of medical resources and disruptions in medical services, highlighting the importance of supply chain management for hospital resilience. This study conducted an online survey of 197 respondents from Chinese public hospitals to investigate the critical effect of supply chain management on the resilience of public hospitals. The analysis results of SEM-PLS indicated that leadership and digital technology capabilities in supply chain management significantly impacted the resilience of public hospitals. In addition, the risk control capability of supply chain management significantly mediated the relationship between leadership, digital technology capabilities, and resilience. The finding of this study provides support for supply chain management and decisionmaking in public hospitals in China and enriches the literature on supply chain management and resilience.